Facile Assembly of a Large‐Area BNNSs Film for Oxidation/Corrosion‐Resistant Coatings. Issue 19 (18th July 2018) - Teng, Chao; Lin, Yucai; Tan, Yanli; Liu, Jian; Wang, Lei
Abstract: Copper is one of the most widely used materials in industrial applications, such as electric power, electronics, and mechanical engineering fields. However, under high humidity, high temperature environment, acid, base, and salt solutions, the copper is vulnerable to destruction, which induces the oxidation and corrosion of copper surface. For circumventing these problems, a robust hydrophobic hexagonal boron nitride nanosheets (BNNSs) coating is facilely prepared through integrating the methods of liquid exfoliation, interface self‐assembly, and physics vapor deposition. The coating can prevent the copper to be oxidized at temperature as high as 500 °C. The corrosive droplets on the coating surface keep in Cassie's state and cannot penetrate into the valley of the topography, which effectively prevents the electrochemical corrosion at the interface between copper and the coating materials even under the DC voltage of 10 V. This finding sheds light on large‐scale constructing of oxidation/corrosion‐resistant coating for copper base materials toward practical industrial application. Abstract : The large volume boron nitride nanosheets (BNNSs) dispersion through a wetting ball milling method is successfully prepared. This strategy quickly converts solvent‐exfoliated BNNSs dispersion into large‐area ultrathin BNNSs film. A robust hydrophobic BNNSs coating is obtained to transfer the interfacially assembled pristine BNNSs film on copper surface combined fluorination treatment, forming an effective resistant oxidation/corrosion coating.